RELEVANCE OF BASIC COMPETENCY OF AUTOMOTIVE LIGHT VEHICLE ENGINEERING EXPERTISE PROGRAM TO WORK COMPETENCY IN THE AUTOMOTIVE MECHANICAL INDUSTRY - Nugroho, Rifa'i Nugi; Kuntadi, Iwa; Mubarak, Ibnu (Universitas Pendidikan Indonesia, 2021)
This research aims to: (1) know the basic competencies needed in the field of mechanical industri, (2) know the exist or absence of basic competencies taught in the TKRO expertise program but needed in the field of mechanical industri, (3) know the exist or absence of basic competencies that are not taught in the TKRO expertise program but are needed in the field of mechanical industri, (4) know the level of relevance of basic competencies in the automotive light vehicle engineering expertise program applied to mechanical work competencies. This research is a quantitative descriptive study with a survey approach. The subjects of this research are teachers who teach productive subjects on the competence of automotive light vehicle engineering expertise Bandung as well as 3 respondents from 3 different agencies. The data retrieval technique used in this study uses questionnaires. The analytical technique used is quantitative descriptive analysis with percentages. The results of this study show that: (1) there is relevance between the competence taught and the competence compiled by the government, (2) The number of competencies from schools that are less relevant to the industri there are 2 competencies, namely the competence to improve rims and present the results of evaluation of 2D and 3D sketches of orthogonal projection standards, (3) The number of basic competencies that have not been accommodated in the automotive light vehicle engineering expertise program to mechanical work competencies consists of 14 additional competencies, (4) there is relevance of the basic competence of the automotive light vehicle engineering productive program between schools, governments and agencies, (5) the level of relevance of basic competencies of automotive light vehicle engineering expertise programs to mechanical work competencies with percentage values (85.52%) which fall into the category is very relevant.